Effect Of Potato Flour Substitution In Making Chocochips Cookies - Kispriatama, Cindy; Gusnita, Wiwik (Universitas Negeri Padang, 2023)
This research is motivated by the lack of variety in processing chocochips cookies and maximizing the potential of local food, especially potatoes. This study aims to analyze the effect of potato flour substitution as much as 15%, 30% and 45% on the quality of chocochips cookies which include shape, color, aroma, texture and taste. This type of research is a pure experiment (true experiment) using a one-factor Completely Randomized Design (CRD) method, namely the use of potato flour (15%, 30% and 45%) with three repetitions. The type of data used is primary data sourced from 5 expert panelists who have provided an assessment through a questionnaire (organoleptic test format). The data that has been obtained are then tabulated and analysis of variance (ANOVA) is performed. If they are different and there is an effect, the Duncan test is carried out. The results showed that potato flour substitution had no significant effect on the quality of shape, color, aroma, and taste. While the significant effect is on the quality of the texture. The results of the test on the quality of the best chocochips cookies were the treatment (X1) with 15% potato flour substitution. For further research, it is recommended to conduct further research on nutritional content or shelf life with the best substitution of potato flour at 15% (X1)